Pengaruh Personal Selling Dan Sales Promotion Terhadap Keputusan Pembelian - Purnama, Denta; Fadillah, Adil (Jurnal Ilmiah Manajemen Kesatuan, 2017)
Personal selling is a direct two way promotion considered more effective in product distribution, as for the final result of a promotion is product sales. Sales promotion is a direct persuasion offering incentives or extra values aimed at creating immediate sales. Purchasing decisions is a buyer’s last step to decide his or her choice to either finally purchase or not the promoted product. We used primary data in this researh. Samples are collected using Slovin’s formula. Data calculation and analysis are using SPSS, multiple linear regression and correlation. The calculation resulted a coefficient for variable X1 for the amount of =0,555. This means that for every 1 point increase in Personal selling will decrease purchasing decision for 0,555 point. While the coefficient for variable X2 is = 0,426, which means that for every 1 point increase in sales promotion will decrease purchasing decision for 0,426 point.